PRELIMINARY INSULATION OF CONCRETE FLOOR SLABS ON GRADE. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1952)
The report presents the results of a study made to determine the need for and effectiveness of edge insulation for concrete floor slabs on grade, for military construction in the New England area. Such insulation may serve the following three possible functions: (1) prevent excessive heat losses at edge of slab and exterior walls, (2) maintain a comfortable floor temperature for personnel occupancy and (3) prevent condensation on floor surface adjacent to exterior walls. (Author)